Предмет: Алгебра,
автор: Аноним
Уравнение и его корни
Приложения:
Ответы
Автор ответа:
0
(2х^2-4)/3(х-1)=(6х+4)/3
2х^2-4=(6х+4)(х-1)
2х^2-4=6х^2-6х+4х-4
6х^2-2х-4-2х^2+4=0
4х^2-2х=0
2х(2х-1)=0
2х=0
х1=0
2х-1=0
2х=1
х=1/2=0.5
2х^2-4=(6х+4)(х-1)
2х^2-4=6х^2-6х+4х-4
6х^2-2х-4-2х^2+4=0
4х^2-2х=0
2х(2х-1)=0
2х=0
х1=0
2х-1=0
2х=1
х=1/2=0.5
Похожие вопросы
Предмет: История,
автор: erkezhanolzhabay
Предмет: Биология,
автор: vkhayrullina09
Предмет: Алгебра,
автор: dashylik18
Предмет: Обществознание,
автор: pandora234
Предмет: Математика,
автор: lizynehka